PERBANDINGAN EKUITAS MEREK SEPATU OLAHRAGA NIKE DAN ADIDAS - Bernard Edwin Silaban; Fitri Andini Marselia (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2016)
Top two brand award 2015 based on Frontier Consulting Group survey for sport shoes gone to Nike dan Adidas. The objective of this research is to see and to compare these top two brands from the view of brand equity elements such as brand awareness, brand association, perceived quality, and brand loyalty. The research method is comparative. Data collection used is questionnaire, and it was spread to 150 students within the region of East of Jakarta such as Institut Bisnis Nusantara, Sekolah Tinggi Manajemen Transportasi Trisakti, dan Universitas Darma Persada. The sampling technique is judgemental sampling and the tools of data analysis used are validity, reliability and cochran’ test. The research conclution from the element of brand awareness, Nike lead Adidas as top of mind. From the view of brand association Nike still lead with 12 components that formulating brand image while Adidas had only 8 components. And based on perceived quality and brand loyalty Nike a little bit better than Adidas but they are still in the same range of good.